Why Only Few Operations Researchers Manage - Beged-Dov, A. G. (Management Science, 1966)
Discussed are some issues which were raised at a session devoted to OR education at the 1964 TIMS-ES Joint European Conference. The central contention of this paper is that the single most reliable indicator of how effective is OR is the proportion of operations researchers who eventually attain general management responsibilities. The main obstacles standing in the way of conducting superior Operations Research are discussed. It is claimed that certain alarming developments in the practice and education of Operations Research must be arrested. Otherwise, the discipline will not be able to effectively solve the more challenging problems of business and society.